Critical care management of a patient with generalized arterial calcification of infancy - Lorenzo Galletti; Ezio Bonanomi; Silviya Khemio Arnes; Lazoryshynetz Vasyl (Ukrainian Journal of Cardiovascular Surgery, 2018)
Abstract: we describe the case of an infant hospitalized in our pediatric intensive care unit with suspected miocarditis. The diagnosis of generalized arterial calcification of infancy (GACI) was confirmed after genetic analysis, the patient was 6 days on extracorporeal membrane oxygenation and died after a failed attempt of endovascular stent placement on 19th day of hospitalization. This paper also contains a review of the literature including new insights into genetic and molecular mechanisms concerning the development of GACI, describe the pathophysiology of the disease and discuss the recent possible ways of treatment and management of GACI.